(4x+3)2-4(x-1)2=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+6\right)\left(3x+1\right)+x^2-36=0\)
\(\Leftrightarrow\left(x+6\right)\left(3x+1\right)+\left(x-6\right)\left(x+6\right)=0\)
\(\Leftrightarrow\left(x+6\right)\left(3x+1+x-6\right)=0\)
\(\Leftrightarrow\left(x+6\right)\left(4x-5\right)=0\)
\(\Leftrightarrow\hept{\begin{cases}x+6=0\\4x-5=0\end{cases}}\Rightarrow\hept{\begin{cases}x=-6\\x=\frac{5}{4}\end{cases}}\)
Vậy \(x=-6;\frac{5}{4}\)
(x^2+x)^2+4(x^2+x)=12
x^4+2x^3+x^2+4x^2+4x=12
x^4+2x^3+5x^2+4x=12
x^3(x+1)+x^2(x+1)+4x(x+1)=12
(x^3+x^2+4x)(x+1)=12
x(x^2+x+4)(x+1)=12
Bạn lập bảng và làm tiếp nhé
(3x + 1)2 - (2x - 5)2 = 0
<=> (3x + 1)2 = (2x - 5)2
TH1 : 3x + 1 = 2x - 5
<=> 3x - 2x = - 5 - 1
=> x = - 6
TH2 : 3x + 1 = - (2x - 5)
<=> 3x + 1 = - 2x + 5
<=> 3x + 2x = 5 - 1
<=> 5x = 4
=> x = 4/5
Vậy x = - 6 hoặc x = 4/5
(3x+1)2-(2x-5)2
(3x+1)2=(2x-5)2
3x+1=2x-5
3x-2x=-5-1
x=-6
Vậy x=-6
\(\Leftrightarrow\left(4x+3\right)^2-\left(2x-2\right)^2=0\)
\(\Leftrightarrow\)\(\left(4x+3+2x-2\right)\left(4x+3-2x+2\right)=0\)
\(\Leftrightarrow\)\(\left(6x+1\right)\left(2x+5\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}x=-\frac{1}{6}\\x=-\frac{5}{2}\end{cases}}\)
\(\Rightarrow x=\frac{-1}{6}\)